Islam dan Budaya: Menelisik Makna Simbol Tradisi Kai'an pada Masyarakat Desa Tanjung Besar Kabupaten Oku Selatan, Indonesia - Syaputri, Intan Kurnia; El Mala, El Mala; Verolyna, Dita (Al-Hikmah Media Dakwah, Komunikasi, Sosial dan Kebudayaan, 2023)
The kai'an tradition is a female circumcision tradition known to the people of South Oku Regency, Tanjung Besar Village, and the Semende Lembak tribe. This research discusses the meaning of symbols found in the implementation of the ka'an tradition in the Tanjung Besar Village community, the Semende Lembak tribe. The research method used in this research is a descriptive-qualitative method; the researcher tries to describe the results of the research that has been carried out. The subjects in this research consisted of four informants, namely the traditional leader, traditional officials, rebiyah, and celebration organizers. Of course, the informants in this research were informants who were in accordance with the specified informant characteristics. Determining informants in this study used purposeful sampling techniques. The data sources in this research use primary and secondary data. The data collection methods in this research are observation, in-depth interviews, and documentation analysis. Analysis of the research results was also carried out using Roland Bhartes' semiotic analysis. From the research results on implementing the Kai'an tradition, there are two stages, namely the preparation stage and the ceremony implementation stage. In the first stage, the header symbol is interpreted as a symbol of protection, can provide positive things, is liked by many people, and has good character. Meanwhile, in the second stage, the symbol of a girl bathing using various media is interpreted as meaning that a girl who is circumcised will later have a clean soul, have nobility and sincerity, be humble, be able to benefit others, be humble, and symbolize elegance.